2016
DOI: 10.1098/rsbl.2016.0022
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator shifts drive petal epidermal evolution on the Macaronesian Islands bird-flowered species

Abstract: Pollinator shifts are considered to drive floral trait evolution, yet little is still known about the modifications of petal epidermal surface at a biogeographic region scale. Here we investigated how independent shifts from insects to passerine birds in the Macaronesian Islands consistently modified this floral trait (i.e. absence of papillate cells). Using current phylogenies and extensive evidence from field observations, we selected a total of 81 plant species and subspecies for petal microscopy and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…Finally, the area of the spots did not exhibit different morphology from the rest of the corolla. The tabular cells observed from cross-sections were similar to those reported previously in S. trifoliata (Ojeda et al 2016). According to these authors petal micromorphology is a labile trait during pollinator shifts.…”
Section: Corolla Spotssupporting
confidence: 87%
See 1 more Smart Citation
“…Finally, the area of the spots did not exhibit different morphology from the rest of the corolla. The tabular cells observed from cross-sections were similar to those reported previously in S. trifoliata (Ojeda et al 2016). According to these authors petal micromorphology is a labile trait during pollinator shifts.…”
Section: Corolla Spotssupporting
confidence: 87%
“…The tabular cells observed from cross‐sections were similar to those reported previously in S. trifoliata (Ojeda et al . ). According to these authors petal micromorphology is a labile trait during pollinator shifts.…”
Section: Discussionmentioning
confidence: 97%
“…Consequently, there is an absence of plant species typically associated with these pollinator groups, and shifts in reproductive traits to become more generalised have been observed (Inoue, ). Similar patterns have been found in Macaronesia (Ojeda et al ., ), Antillean Islands (Martén‐Rodríguez et al ., ), among others (for example New Zealand, Juan Fernandez, Hawai'i, Mascarenes) suggesting that a shift to generalised pollination syndromes is common among island floras (Olesen & Valido, ).…”
Section: Functional Disharmonymentioning
confidence: 99%
“…Several recent reports have shown that some flowers manipulate pollinators by selective loss of these cells. Ojeda et al (2016) analysed petal epidermal micromorphology for plants on the Macaronesian islands, and found that, in all five independent cases of transition to bird pollination, conical epidermal cells were lost. This evolutionary change is postulated to minimize nectar robbing by insects, by making the petal surface more slippery.…”
Section: Conical Cells Grip and Slipmentioning
confidence: 99%